Climate risk and corporate cash holdings: Mechanism and path analysis - Yu, Siming; Wang, Lei; Zhang, Shuocheng (Frontiers in Environmental Science, 2022)
Based on climate change data of local cities and cash holding data of Chinese listed companies from 2011 to 2019, this paper studies the impact of climate change on the level of corporate cash holdings and analyzes the path of climate change on corporate cash holding level. The results show that: under the influence of climate change, enterprises hold high level of cash holdings to cope with risks, and change variables to carry out robustness tests, the results remain consistent; By analyzing the source channel of enterprise cash, it is found that climate change increases the cash received from selling goods, providing services and tax refund, but decreases the cash received from borrowing. The mechanism of action shows that climate change has increased the operating risk of enterprises and thus the level of cash holdings of enterprises, but climate change has not increased the financial risk of enterprises. The main reason is that under the influence of climate change, enterprises have reduced the debt level and thus reduced the financial risk. Heterogeneity analysis shows that the impact of climate change on corporate cash holdings is more obvious in state-owned enterprises, enterprises with high degree of financing constraints and ecologically fragile regions. This study provides a new explanation for the influencing factors and approaches of corporate cash management strategies, which helps to better understand the cash holding strategies of listed companies in China. It also indicates that climate change is likely to be a macro incentive to aggravate the risks of the real economy.